Airborne Grass Pollen and Ambient Phl p 5 Aeroallergen in Évora (south Portugal), 2009-2011 - C. M. Antunes (2012)
lhese resuíts show that Phl p 5 is prelerenlially associated with pollen grains, allhough a small percentage may also be lound in smaller partiele sizes. lt was recorded a yearly varialion in airlJorne pollen and Phl p 5. The highest polency pollen was recorded in 2009 bul the highesl load ln aeroallergen was registered in 2011. ln conclusion, aeroallergen quantification together wilh airborne pollen counts, may contribute to a betier understanding 01 lhe exposure leveis lo airlJome pollen allergens.